Safe Contact Lens Practices during Coronavirus (COVID-19) Pandemic - Bhattarai, Sanjeev (Nepal Mediciti Medical Journal, 2021)
World is threatened by different variants of Coronavirus to an extent that life has been jeopardized in all services including eye care facility. Contact lenses which are one of the preferred modes of vision correction are not an exception to COVID-19 infection. Recently there is confusion among practitioners and patients regarding the safety of contact lens use during COVID-19. This review article summarizes the current recommendations and findings regarding contact lens use during COVID-19. Though eye health professionals and contact lens users are at risk to contract Coronavirus, with proper care, maintenance and disinfection techniques, it would be safe to continue wearing contact lenses. There is currently no strong evidence to suggest that contact lenses are not safe to wear during COVID 19 times. Eye care practitioners responsible for contact lens application must wear special surgical masks, protective glasses or visors and disposable waterproof gloves. Regarding soft contact lenses, preferably daily disposable lenses should be used from the sterile packages. Similarly for rigid gas permeable lenses, lenses made up of fluoropolymer contained in sealed packages must be motivated for the individuals. Since the infected hands can bring the virus to the eyes, contact lens users should avoid touching the nose, mouth and eye unnecessarily. Contact lens after each use must be disinfected with hydrogen peroxide solutions with a special catalyst container. In the case of eye redness and Flu like symptoms, contact lens trial and wearing practices should be suspended or postpone till the condition becomes normal. To minimize the contact time between the patient and examiner soft copy of the instruction sheet, teleconsultation should be motivated. Though the eye is an unlikely site for Coronavirus infection, eye doctors should warn the contact lens wearers to follow scrupulous contact lens hygiene rules.